Performing Ireland: Now, then, now …. Issue 1 (1st December 2020) - Kelly, Marie; O'Gorman, Siobhán; Phillips, Áine
This article offers a comprehensive, research-informed reflection on the contents of the Special Double Issue of Scene, 'Performance and Ireland', conceptualized within a sense of looped temporalities (now, then, now), a concept borrowed from Irish multidisciplinary performance company, ANU Productions. From the perspectives of performance studies and visual culture, we connect and contextualize for an international readership articles concerning such topics as: Ireland's colonial history; race, ethnicity and racism in relation to Ireland; performing the Irish diaspora; feminist activism; performing LGBTQ+ identities; the Troubles and the border in Northern Ireland; Ireland as a global brand; the Gaelic Athletics Association (GAA); and artistic engagements with hidden histories. This introductory article provides an overview of the discourses on performance studies and Ireland to date, and draws on theories of performance as they intersect with Irish studies, postcolonialism, commemoration and gender and sexuality, to situate the volume within pertinent contemporary and historical contexts from the Irish Famine (1845‐49) to Covid-19. 'Performing Ireland' in the context of the current pandemic is considered specifically towards the end of the article.